A variety of clinical presentations of eosinophilic granulomatosis with polyangiitis: a comprehensive review - Agata Sebastian; Joanna Kosałka-Węgiel (Rheumatology)
Introduction Eosinophilic granulomatosis with polyangiitis (EGPA) is characterized by eosinophilic granulomatous vasculitis. Typical symptoms include late-onset bronchial asthma and blood and tissue eosinophilia. In addition to these characteristic symptoms, EGPA can affect important organs such as the skin, kidneys, heart, sinuses, gastrointestinal tract, and nervous system. Given the variability of the clinical presentation, EGPA is challenging to diagnose. Furthermore, EGPA often occurs in phases, with clinical manifestations and pathological findings varying depending on the affected anatomic site and stage of disease.